Building effective research policy networks: linking function and form - Mendizabal, Enrique (ODI, 2006)
This paper looks at the factors that affect the key structural characteristics of research policy networks in an attempt to develop a methodology for studying and understanding what networks do and how. It builds on previous work on the roles and functions that networks carry out and focuses on their structural characteristics. The literature on networks is explored to identify the main and most common factors affecting their structure, and then the paper considers the possible effects of these structural factors on a network's ability to perform one or more of these functions based on some of the lessons learned from a study of seven research policy networks in Peru. The paper provides a menu of factors and characteristics worth considering when intending to build effective networks.
OCLC: 183914885

Understanding Networks: The functions of research policy networks - Mendizabal, Enrique (ODI, 2006)
We are constantly talking about networks. Banks use their networks to offer global services to customers; airlines fly passengers all over the world via their networks of partners; news agencies use media networks to keep us informed every minute of the day; and terrorist networks threaten citizens around the world. The importance of networks extends to the development sector: they organise civil society to advocate for and implement change; they link the local with the global, the private with the public; and they provide spaces for the creation, sharing and dissemination of knowledge. In a way, networks seem to make anything and everything happen. But we have yet to understand what they are and what they can and cannot do. In the development literature, a huge variety of policy and social network concepts and applications exists. This paper attempts to set out a framework to help clarify what research policy networks do.

The Alignment, Interest and Influence Matrix (AIIM) guidance note - Mendizabal, Enrique (ODI/RAPID, 2010)
In 2007, on the eve of a workshop to introduce a new version of the RAPID approach to DFID policy teams, Enrique Mendizabal and Ben Ramalingam created the Alignment, Interest and Influence Matrix (AIIM), a stakeholder analysis tool that not only helps to identify key stakeholders, but also suggests a possible course of action towards them.

Not everything that connects is a network - Hearn, Simon; Mendizabal, Enrique (ODI, 2011)
In the public policy context, networks have been predominant factors in policy formulation, innovation and global governance. While not a new phenomenon in the development landscape, networks are becoming increasingly prevalent. Donors, for example, are turning to networks to deliver aid interventions, NGOs are working through networks for collective advocacy and researchers collaborate across networks for greater policy influence. But are networks always the most appropriate vehicle? Where they are appropriate, how can we make the best use of them? This Background Note argues for a more rigorous understanding of their nature, particularly their value (and costs), and presents a revised Network Functions Approach as a model for rationalised investment in networks.

Strengthening humanitarian networks: Applying the network functions approach - Ramalingam, Ben; Mendizabal, Enrique; Schenkenberg van Mierop, Ed (ODI, 2008)
This note offers a simple, flexible and powerful methodology — the network functions approach (NFA) — that can be applied to analyse and strengthen humanitarian and development networks. Based on research undertaken at ODI and elsewhere, the NFA suggests there are six overlapping functions that different networks perform in varying combinations. Through reflection on a network’s current activities and how they relate to each of these functions, the NFA helps those facilitating, acting within or supporting networks to work towards an ‘ideal’ functional mix. The aim is for network strategies to be honed, thinking clarified, activities sharpened and ultimately, humanitarian performance improved.